The Ways to Develop Indonesian Learning Material Enriched by Local Culture for Foreign Students - Laily Nurlina; Andayani Andayani; Retno Winarni; St.Y. Slamet (BIRCU, 2020)
Mastering Indonesian language is a crucial thing although it is not one of requirements to study in Indonesia. The foreign students need to speak in Indonesian language because people like to communicate in same language. That’s why many Indonesian Language Teaching Institutions for Foreign Students (ILTIFS) provided some services to conduct Indonesian learning especially in Central Java- Indonesia. This study is purposed to describe an effort to develop Indonesian learning material for foreign students enriched by local culture. Learning language means learning its culture, foreign students need to know local culture so they can communicate contextually and avoid from shock culture in early living here. The paper used qualitative description to explain four steps on developing learning material.